A human capital‐based framework of career, well‐being, and social information reasons for managerial lateral job assignment preferences. Issue 4 (5th December 2021) - Campion, Emily D.; Campion, Michael A.; Campion, Michael C.
Abstract: Research on job assignments has generally assumed employees will accept assignments when offered. In this study, we examine managerial preferences for potential job assignment opportunities conceptualized using human capital theory to provide a holistic understanding of this phenomenon. Using two pilot studies, we refine the list of reasons managers use when forming lateral assignment preferences. In the main study, we collected data from a representative sample of more than 1200 managers in a large US organization who provided preferences for all possible assignment locations (about 40) in their regions and reported reasons for their preferences. Results showed career development reasons (e.g., promotion potential, opportunity to learn) and social information reasons (e.g., location manager, customers) attracted managers to assignments, and health and well‐being reasons (e.g., commuting, stress) repelled managers. There were several differences in these relationships by managerial level such that health and well‐being reasons were more important than career development reasons for lower‐level managers than higher‐level managers, who seemed to generate their preferences based more evenly on both types of reasons. We ask whether gender moderates the relationship between health and well‐being reasons and preferences and find little support. We also explore whether manager racioethnicity moderates the relationship between community racioethnicity and preferences and find a few differences. Most findings were replicated when predicting actual movement 2 years later. Results suggest managerial preferences should consistently be considered in job assignment research and that organizations should obtain and use preference data when making internal staffing decisions.